PEDAGOGY COURSES: DIGITAL TECHNOLOGIES AND SOCIAL JUSTICE - Guedes Martinez, Dayra Emile [UNESP]; Bizelli, Jose Luis [UNESP]; Reis, Marcia Lopes [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The social and economic relevance of digital information and communication technologies (DICT) encourages basic education to consider them, under the aegis of social justice, since school is the place for the full development of the individual. This work aims to analyze the political-pedagogical projects (PPP) of the Pedagogy courses at UNESP Araraquara campus, UNICAMP and USP Sao Paulo campus - highlighting the references and disciplines on DICT and social justice. It was possible to verify that social justice is considered by the analyzed institutions and that there is availability of subjects, in their majority, optative on digital technologies, however, the projects, which represent the intentionality of the pedagogical action, do not present explicit evidence that DICT is used and studied from the perspective of social justice.
Keywords: Pedagogy course; Political-pedagogical project; Digital information and communication technologies; Social justice